Diagnostic power of the non‐ischaemic forearm exercise test in detecting glycogenosis type V. (5th March 2015) - Hogrel, J.‐Y.; van den Bogaart, F.; Ledoux, I.; Ollivier, G.; Petit, F.; Koujah, N.; Béhin, A.; Stojkovic, T.; Eymard, B.; Voermans, N.; Laforêt, P.
<x xml:space="preserve">Abstract</x> Background and purpose This was a retrospective study to assess the diagnostic value of the non‐ischaemic forearm exercise test in detecting McArdle's disease. Methods The study is a retrospective diagnostic study over 15 years (1999–2013) on a referred sample of patients suffering from exercise intolerance and various muscle complaints, generally with elevated creatine kinase (CK). In all, 1226 patients underwent the non‐ischaemic forearm exercise test. Blood lactate, ammonia and CK levels were analyzed. DNA analyses and/or muscle biopsies were assessed to confirm the diagnosis of McArdle's disease. The results of 60 volunteers were used to compare with the results of study subjects. Results In this cohort, 40 patients were finally diagnosed with McArdle's disease. Absolute values of lactate and ammonia rise were used to discriminate all McArdle patients from healthy patients. A sensitivity and specificity of respectively 100% and 99.7% were calculated. The 24‐h CK level showed no significant difference from the CK level at the day of the test and confirms the safety of the test. Conclusions This study has formally assessed the diagnostic value of the non‐ischaemic forearm exercise test in the detection of McArdle's disease. Very high sensitivity and specificity were observed. Furthermore, the test is easy to set up and to perform, it is non‐traumatic and cost effective. It may circumvent a muscle biopsy in McArdle patients presenting the most common mutations. Hence, it is a perfect and safe screening instrument to detect patients with McArdle's disease. Glycogen storage disease type III patients, however, may show similar patterns to McArdle patients.